Preparation and Characterization of 49% Poly(Methyl Methacrylate) Grafted Natural Rubber (MG49)-Stannum (IV) Oxide (Sn02)-Lithium Salt Based Composite Polymer Electrolyte - Ahmad A.; Rahman M.Y.A.; Harun H.; Su'ait M.S.; Yarmo M.A. (2023)
49% poly(methyl methacrylate) grafted natural rubber (MG49) in the presence of 4% wt. stannum (IV) oxide (Sn02) and lithium salts (lithium tetrafluoroborate, LiBF4 and lithium perchlorate, LiCl04) in composite polymer electrolyte (CPE) films has been prepared. The MG49-Sn02 polymer electrolyte films were prepared via solution casting technique at different concentrations ranging from 0% wt. to 30% wt. The effect of the lithium salt concentration based on morphological observation, structural, chemical interaction and ionic conductivity studies of MG49-Sn02 composite polymer electrolytes film have been studied. Morphological observation showed that Sn02 nanoparticles were well dispersed in MG49 films. The addition of lithium salts has changed the topological texture from a smooth and dark surface to a rough and bright surface. The structural observation showed that complexation and re-crystallization have occurred in the system. FTIR and XPS analysis confirmed that some interaction between lithium ion and oxygen atoms were observed at the carbonyl (C=O) (1730 cm-1-1710 cm-1) and ether group (C-O-C) (1300 cm-1-950 cm-1). The highest ionic conductivity was given by 30% wt. LiBF4 at 1.6 10-6 S cm-1 in comparison to LiCl04 was 6.0 10-8 S cm-1 at 20% wt.. The conductivity of MG49-Sn02-LiCl04 obeys the Arrhenius equation in temperature range from 303 to 373 K with the pre-exponential factor, so of 5.33 10-2 S cm-1 and the activation energy, Ea of 0.25 eV. On the other hand, MG49-Sn02-LiBF4 exhibited non-Arrhenius-like behaviour at the same temperature range. The electrochemical stability of MG49-Sn02-LiCl04 has been found to maintain its shape even after the 100th cycle in the range of -2.0 to +2.2 mV and -8.0 to +6.0 mV for MG49-Sn02-LiBF4. 2012 by ESG.